Potential Contribution of Exosomes to the Prion-Like Propagation of Lesions in Alzheimer’s Disease - Vingtdeux, Valerie; Sergeant, Nicolas; Buee, Luc (Frontiers in Physiology, 2012)
Since the discovery of prion diseases, the concept that a transmissible pathogen could be a protein has emerged. As such, this transmissible protein agent can transfer its pathological mis-folded shape to the same but normally folded protein thus leading to the propagation of a disease. This idea is now extrapolate to several neurological diseases associated with protein mis-folding and aggregation, such as Alzheimer’s disease. Alzheimer’s disease (AD) is a slowly developing dementing disease characterized by the coexistence of two types of lesions: the parenchymal amyloid deposits and the intraneuronal neurofibrillary tangles (NFT). Amyloid deposits are composed of amyloid-beta peptides that derive from sequential cleavages of its precursor named amyloid protein precursor. Neurofibrillary tangle is characterized by intraneuronal aggregation of abnormally modified microtubule-associated Tau proteins. A synergistic relationship between the two lesions may trigger the progression of the disease. Thus, starting in the medial temporal lobe and slowly progressing through temporal, frontal, parietal and occipital cortex, the progression of NFT is well correlated with clinical expression of the disease. However, little is known about the mechanism driving the spatiotemporal propagation of these lesions ultimately leading to the disease. A growing number of studies suggest a prion-like diffusion of amyloid deposits and NFT. In the present chapter, we will develop the current hypotheses regarding the molecular and cellular mechanisms driving the development and spreading of Alzheimer disease lesions from the window of multivesicular bodies and exosomes.